Noninvasive assessment of the activity of the shoulder girdle muscles using ultrasound real-time tissue elastography. Issue 5 (October 2015) - Ishikawa, Hiroaki; Muraki, Takayuki; Sekiguchi, Yusuke; Ishijima, Takahiro; Morise, Shuhei; Yamamoto, Nobuyuki; Itoi, Eiji; Izumi, Shin-Ichi
Abstract The purpose of this study was to clarify whether the activity of the shoulder girdle muscles could be estimated by measuring the elasticity of these muscles under several levels of muscle contraction through ultrasound real-time tissue elastography (RTE). Ten healthy men performed submaximal voluntary contractions (MVC) in each manual muscle testing position for the middle deltoid, upper trapezius, supraspinatus, levator scapulae, and rhomboid major. The elasticity of these muscles was measured using ultrasound RTE during the task. The strain ratio of the muscle to an acoustic coupler was calculated as an assessment index of the muscle elasticity. Higher strain ratio values imply lower elasticity. In addition, the electromyographic activity was recorded from surface electrodes attached only to the middle deltoid and upper trapezius. The strain ratios were negatively correlated with the normalized root mean square values for the middle deltoid (r = −0.659, p < 0.001) and upper trapezius (r = −0.554, p < 0.001). The strain ratios of all the muscles decreased with an increase from 10% MVC force to 30% MVC force. Ultrasound RTE may be useful for noninvasively assessing the activity of the shoulder girdle muscles at certain shoulder positions with low levels of muscle contraction.